Unregulated carbon emissions in tribal South Gujarat and remedial measures - Xavier, Jothi F. (Social Action: A Quarterly Review of Social Trends)
This paper investigates the environmental and social impacts of unregulated jiggery making units, brick clines and stone quarries in the tribal$1 (Bs regions of south Gujarat particularly in the tacks of Umarpada, mongrel, and madvi in Surat district. Reproduced s
Keywords: Jagery making units, brick kilns and stone quarries, Advise communities, Carbon emission, Air pollution and soil degradation, Organic farming, Cash crops, sugarcane cultivation, Stubble bruin, Tribal herbal medicine, Respiratory illness, Eco-friendly and low-cost architecture, medicine, Respiratory illness, Eco-friendly and low cost architecture, indigoes knowledge, Flash, Land leasing, Sickle cell anemia .